PERTIMBANGAN DEMOGRAFIS DI TENGAH PANDEMI COVID-19: KEBIJAKAN PEMBATASAN PERJALANAN KE PROVINSI PAPUA - Jevon E.M Nahuway; Johni Korwa (Research Centre for Population, Indonesian Institute of Sciences, 2020)
This paper aims to analyze travel restriction policy to Papua in the midst of the COVID-19 pandemic through a demographic lens. It finds that the travel restriction policy to Papua was not only influenced by non-demographic factors including politics, economy, health, but also by demographic factors such as mortality, fertility, and migration. There are several reasons for this. Firstly, the population of Papua remained small in comparison with other provinces across Indonesia; thereby imposing travel restrictions were in the best interest to lower the mortality rate in Papua due to COVID-19. Secondly, preserving fertility during the COVID-19 pandemic was vitally important regarding future generations and the government of Papua had demonstrated its ability to handle the situation by appointing several health centers particularly for pregnant women. Thirdly, people moving in and out of Papua currently became inevitable, thus migration should be limited for a while through the travel restriction policy.